Ancient and Modern Approaches to the Problem of Relativism - Davis, Matthew K. author. aut Link
VII, 133 p. 1 illus.
Keywords: “This ambitious study brings together three great thinkers of ancient and modern times—Husserl, Locke, and Plato—in a careful analysis of the problem of knowledge, of what the unassisted human mind can know and how it may know what it does. I know of no other work that even attempts to do what this study does so well: to bring into respectful but critical dialogue with one another these three philosophers on the question “what is knowledge?”” --Robert C. Bartlett, Behrakis Professor in Hellenic Political Studies, Boston College, USA Relativism, or the claim that it is possible that the appearances and opinions of each of us are correct for each of us, and hence that any view is as true as any other, has remained a continuing problem for philosophy and science for 2,500 years. Today, because of the widespread acceptance of relativism, the problem is greater than ever before. This book argues that Plato in fact solved this problem. In the first two chapters, by means of a study of Husserl and Locke, Davis shows that it is possible to return to and take seriously Plato’s treatment of this problem. The third chapter presents Plato’s solution to it. This book is distinctive in that it shows that a problem that has been thought to be present throughout the history of Western thought was in fact solved by Plato, and in that it shows that we can, beginning from our contemporary situation, return to Plato’s solution. Matthew K. Davis is former Dean and Director of Graduate Programs at St. John's College, Santa Fe, USA, where he has taught for twenty-five years.